Webinar: Pencegahan Stunting Pada Remaja Di MAN 2 Surakarta - Puspitasari, Dyah Intan; Hanifah, Dina Nur; Persada, Tashila Zahra (Universitas Muhammadiyah Surakarta, 2024)
Adolescents who have poor nutritional status, rarely eat breakfast, consume less fruit and vegetables, and have low knowledge of stunting can be risk factors for giving birth to stunted babies in the future. One strategy that can be done to increase student knowledge is through the provision of education in the form of webinars. The webinar activity with the theme